2019
DOI: 10.3892/etm.2019.7912
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid suppresses colon cancer cell activity in vitro

Abstract: The aim of the present study was to elucidate the underlying mechanism of antitumor activity of gambogic acid (GA) in colon cancer. Human colon cancer SW620 cells were divided into five treatment groups, including no-treatment control (NC), low dose GA (10 µg/ml), medium dose GA (50 µg/ml), high dose GA (100 µg/ml) and 5-fluorouracil (10 µg/ml). Differences in cell proliferation, apoptosis and cell cycle, invasion, and migration were measured between groups using MTT, flow cytometry, transwell and wound-healin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Chen et al confirmed that MAG reduces the level of MMP-9 mRNA through the suppression of the MEK/ERK signaling pathway and thus reduces renal cancer metastasis [46]. Likewise, Zhou and Ma described a decrease of invasion and migration as well as decreased MMP-2 and MMP-9 mRNA in SW620 colon cancer cells treated with GA [47]. We previously described a decrease in MMP-9 and MMP-2 mRNA expression and enzymatic activity in breast (MCF-7), cervical (HeLa), lung (A549), and bladder (T24) cancer cells treated by aminoalkanol xanthone derivatives [23].…”
Section: Discussionmentioning
confidence: 93%
“…Chen et al confirmed that MAG reduces the level of MMP-9 mRNA through the suppression of the MEK/ERK signaling pathway and thus reduces renal cancer metastasis [46]. Likewise, Zhou and Ma described a decrease of invasion and migration as well as decreased MMP-2 and MMP-9 mRNA in SW620 colon cancer cells treated with GA [47]. We previously described a decrease in MMP-9 and MMP-2 mRNA expression and enzymatic activity in breast (MCF-7), cervical (HeLa), lung (A549), and bladder (T24) cancer cells treated by aminoalkanol xanthone derivatives [23].…”
Section: Discussionmentioning
confidence: 93%
“…Consistently, the in vitro experiments also demonstrated a repressed level of miR‐21, weakened migration, proliferation and invasion, and amplified apoptosis in HT‐29 cells after GA treatment, all of which were reversed via overexpression of miR‐21. In a similar light, GA exerts inhibitory effects on the cell viability of colon cancer cells in vitro (Zhou & Ma, 2019). The latter pieces of evidence illustrate the regulatory effect of GA on the proliferation, survival, angiogenesis, invasion, and metastasis of tumors (Gupta et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…CC is a high-incidence malignant tumor with a poor prognosis. Although targeted drugs can improve the prognosis of patients with CC, the mortality rate among patients remains high ( Zhou and Ma, 2019 ). Therefore, reliable biomarkers must be identified for constructing a prognostic model to assess the prognosis and survival of CC patients.…”
Section: Discussionmentioning
confidence: 99%